1991
DOI: 10.1161/01.cir.83.6.2111
|View full text |Cite
|
Sign up to set email alerts
|

Coronary vasoconstriction induced by vasopressin. Production of myocardial ischemia in dogs by constriction of nondiseased small vessels.

Abstract: Thus, vasopressin produces myocardial ischemia by constricting small, nondiseased coronary arteries severely enough to overcome the competition from normal coronary regulation, and this ischemic event is not mediated by prostaglandin products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…ECG changes induced by vasopressin indicated a subendocardiac ischemia (17). Vasopressin is considered to be a vasoconstrictor of the coronary artery (18). An increase in oxygen supply due to coronary vasodilatation or antispasmodic action is crucial to inhibit these ECG changes.…”
Section: Discussionmentioning
confidence: 99%
“…ECG changes induced by vasopressin indicated a subendocardiac ischemia (17). Vasopressin is considered to be a vasoconstrictor of the coronary artery (18). An increase in oxygen supply due to coronary vasodilatation or antispasmodic action is crucial to inhibit these ECG changes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, V1a-dependent vasoconstriction that increases afterload, ventricular stress, 25 and cardiac hypertrophy 26 may result in systemic vascular resistance and a decrease in cardiac output and contractility. 27 Several investigators have shown a V1a receptor-mediated coronary vasoconstrictor response to vasopressin, 28 which is an effect that seems to be dose dependent. The activation of V1b receptors may play an additional role.…”
Section: Clinical Researchmentioning
confidence: 99%
“…Moreover, pharmacological doses of AVP reduce cardiac output independently of the increase in coronary vascular resistance. [15]. Lastly, in isolated rat heart, when coronary perfusion is maintained constant, low concentrations of AVP enhance the myocardial contractility, whereas an opposite effect is observed at high AVP concentrations (500 pg/mL) [16].…”
Section: Discussionmentioning
confidence: 96%